A PRODUÇÃO DO CONHECIMENTO E A FORMAÇÃO DE INDIVÍDUOS REFLEXIVOS TENDO COMO PROPOSTA PEDAGÓGICA O LIVRO DIDÁTICO - Zambon, Vanessa W.; Guerin, Lidiane M.; Kinalski, Alvina C. (Salão do Conhecimento, 2013)
Resumo